(untitled) (Research, Society and Development, 2024)
This study aimed to evaluate the impact of applying Investigative Didactic Sequences and Active Methodologies on learning about snakes, in a 2nd grade high school class at a public school in Curral de Cima, Paraíba. Three investigative didactic sequences were developed and applied to 31 students in the second year of high school in a public school in Paraíba. The strategies developed included group research, discussions on educational materials development, and digital tools use, which provided students with active participation in the learning process. The results showed that these activities not only increased students’ understanding of snakes but also aroused interest in the topic and greater responsibility for their learning, in addition to strengthening their awareness of the importance of snake conservation. In conclusion, the study showed that active methodologies, by encouraging an investigative and participatory approach, not only expanded understanding of the topic but also cultivated critical thinking and scientific curiosity, contributing to a deeper environmental awareness and connecting to students’ daily lives.